Analysis of accounting information systems of cash receipts and cash distributions at UD. AB Bakery Tebing Tinggi - Vina Winda Sari (Institute of Computer Science (IOCS), 2022)
UD. AB BAKERY is a small company that still counts home business or also known as Home Industry, this is because the owner still uses the land where he lives as a place his efforts. UD. AB BAKERY is engaged in the world of deep bread production packaging since the beginning of January 2013. This business produces or processes raw materials into a ready-to-eat product in the form of food light. Not only producing, the owner of this business also directly selling consumer products. UD. AB BAKERY was founded by Mr. Apriansyah with the address on the street of the Association of Lk. IV Kel. Tebing Tinggi Kec. Padang Hilir City of Cliffs Tall.Accounting information systems are very important to be implemented in any business sector, including UD. AB BAKERY. Utilization of the accounting information system provides accurate information about recording cash in and cash out. Accounting information systems are also useful for minimizing cash recording errors, which can affect the future of the company.Cash receipts and disbursements accounting system at UD. ABBAKERYTebing Tinggi has not been carried out systematically,where all processes of cash receipts and cash disbursements are still in progressnote or write in a receipt sheet or bill. UD. AB BAKERY does not perform separation of financial functions,warehouse function and production function so that it is prone to errors –error in recording cash. Internal control system at UD. AB BAKERY yet maximally because there is no segregation of functionsclearly.